The utility of early developmental assessments on understanding later nonverbal IQ in children who are deaf or hard of hearing. (January 2017) - Meinzen-Derr, Jareen; Wiley, Susan; Phillips, Jannel; Altaye, Mekibib; Choo, Daniel I.
Abstract: Objective: In children who are deaf or hard of hearing (DHH), it is helpful to have meaningful early measures of development in order to provide effective interventions and offer benchmarks that help recognize varied developmental trajectories. The main objective of this study was to compare results of an early developmental assessment prior to 3 years of age to later nonverbal IQ assessed between 3 and 6 years of age in children who are DHH. Methods: This study included children 3–6 years of age with bilateral permanent hearing who were enrolled in a prospective cohort study on developmental outcomes. As part of the study, children received the Leiter International Performance Scale-Revised, which provided a nonverbal Brief IQ, as well as standardized language assessment and behavioral checklists. Children were included in this analysis if they had received an early developmental assessment with the Gesell Developmental Schedules-Revised as part of a clinical visit with a developmental pediatrician. Correlation coefficients and multiple regression analysis were used to associate the scores on the Gesell (using a developmental quotient) with scores on the Leiter-R Brief IQ. Results: Forty-five participants who enrolled in the observational study had available evaluation results from the Gesell and complete Brief IQ results from the Leiter-R. The adaptive domain of the Gesell had good correlation (r = 0.61, p < 0.0001) with the Brief IQ on the Leiter-R. Children who had stable developmental or intelligence classifications based on scores (<70, 70 to <85, 85 to <100, ≥100) over time were older (>24 months) at the early Gesell assessment. Degree of hearing loss or maternal education did not appear to confound the relationship between the Gesell and the Leiter-R. Conclusions: The adaptive domain of the Gesell Developmental Schedules – Revised administered in early childhood (under 3 years of age) has good correlation with the nonverbal Brief IQ on the Leiter International Performance Scale-R. Because children who are DHH have a higher likelihood of having a developmental disability compared to the general population, early developmental assessments are often important. Although early developmental assessments have their limitations, our results indicate that they are fairly robust indicators of later development. Such early indicators can be extremely useful in the clinical and educational management of children who are DHH.